Frequency of Vitamin B12 and Red Cell Folate Deficiency in Macrocytic Anaemia - Tanweer Ahmed,; A. Sabeen Rahman,; Shaista Ahmed,; Afshan Siddiqui,; Aisha Javed,; Jawed Kamal ,; Laeeq Ahmed, (Journal of Basic & Applied Sciences, 2021)
Background: Macrocytosis refers to a condition in which red blood cells are larger than normal, with or without anemia. Macrocytic anemia occur due to variety of illnesses and requires further clinical and laboratory assessment. Both folate and vitamin B12 have been known to cause macrocytic anemia since the deficiencies of these two vitamins are very common in Pakistan, it would be imperative to investigate their role in causing megaloblastic anemia. Objective: To determine the frequency of vitamin B12 and folate deficiencies in cases of macrocytic anemia. Material and Methods: This is a descriptive cross-sectional study conducted in the | department of medicine of Abbasi Shaheed hospital from January 2012 to June 2012. A total of 95 patients (65 males and 30 females) with an age of above 13 years, who admitted with macrocytic anemia (MCV>96) with hemoglobin < 12 mg/dl in females and < 13 mg/dl in males were enrolled and data pertaining to complete blood count, serum level of vitamin B12 and RBC folate were analyzed. Result: A total of 95 patients (65 males and 30 females) with hemoglobin < 12 mg/dl in females and < 13 mg/dl in males were taken. Mostly were non vegetarian and majority of the patients belongs to age group of 34-54 years. It was found that 69 patients (48 males and 21 females) from total of 95 had vitamin B12 deficiency which is 72.6% and 43 patients (20 males and 23 females) from total of 95 had folate deficiency which is 45.26%. Conclusion: Our study concludes that vitamin B12 is a major contributing factor of macrocytic anemia in our population. Dietary insufficiency, poor absorption and increase demand might be contributing to high prevalence of vitamin B12 deficiency in our population. Therefore our medical community should seriously consider the merit of early screening for vitamin B12 deficiency and take precautions against the clinical consequences of vitamin B12 deficiency.